Variability in the mating calls of the Lusitanian toadfish Halobatrachus didactylus: Cues for potential individual recognition - Amorim, Maria Clara Pessoa (2012)
The mating sounds (boatwhistles) of nesting batrachoidid Halobatrachus didactylus males were recorded in the Tagus Estuary from piers. Thirteen males with 16 boatwhistles per fish were analysed for 20 acoustic features. All variables showed larger between-male than within-male variation and differed significantly among individuals. Discriminant function analyses (DFA) considering seven of these variables assigned 90–100% of boatwhistles to the correct individual, depending on the number of males and number of sounds per male included in the model. The acoustic features that consistently best discriminated individuals were the dominant frequency of the middle tonal segment of the boatwhistle (P2) and dominant frequency modulation, followed by P2 pulse period, amplitude modulation and sound duration. These results suggest the possibility of individual recognition based on acoustic cues.